Exploring Nurse and Patient Experiences of Developing Rapport During Oncology Ambulatory Care Videoconferencing Visits: Qualitative Descriptive Study - Paula D Koppel; Jennie C De Gagne; Sharron Docherty; Sophia Smith; Neil S Prose; Terri Jabaley (JMIR Publications, 2022)
BackgroundAlthough videoconferencing between oncology patients and nurses became routine during the pandemic, little is known about the development of clinician-patient rapport in this care environment. Evidence that virtual visits may challenge nurses' ability to form connections with patients, demonstrate empathy, and provide support suggests that videoconferencing may not ensure optimal care for persons with cancer. Establishing rapport during videoconferencing visits (VCVs) is important in oncology nursing, as rapport enables the nurse to provide emotional support and assistance to patients as they navigate their cancer journey. ObjectiveThis study investigated the nature of nurse-patient rapport in ambulatory cancer care videoconferencing telehealth visits. Objectives included exploring (1) how patients with cancer and nurses describe experiences of and strategies for cultivating rapport and (2) similarities and differences between rapport in videoconferencing and in-person visits (IPVs). MethodsIn this qualitative descriptive study, interviews were conducted from October 2021 to March 2022 with 22 participants, including patients with cancer (n=10, 45%) and oncology nurses (n=12, 55%), about their experiences of rapport building during VCVs. All interviews were analyzed using conventional content analysis. Data from nurses and patients were analyzed separately using identical procedures, with a comparative analysis of patient and nurse results performed in the final analysis. ResultsMost patients in the study had experienced 3-5 video visits within the past 12 months (n=7, 70%). Half of the nurse participants (n=6, 50%) reported having participated in over 100 VCVs, and all had experiences with videoconferencing (ranging from 3 to 960 visits) over the past 12 months. In total, 3 themes and 6 categories were derived from the patient data, and 4 themes and 13 categories were derived from the nurse data. Comparisons of themes derived from participant interviews identified similarities in how nurses and patients described experiences of rapport during VCVs. Three themes fit the collective data: (1) person-centered and relationship-based care is valued and foundational to nurse-patient rapport in oncology ambulatory care regardless of how care is delivered, (2) adapting a bedside manner to facilitate rapport during VCVs is feasible, and (3) nurses and patients can work together to create person-centered options across the care trajectory to ensure quality care outcomes. Barriers to relationship building in VCVs included unexpected interruptions from others, breaks in the internet connection, concerns about privacy, and limitations associated with not being physically present. ConclusionsPerson-centered and relationship-based approaches can be adapted to support nurse-patient rapport in VCVs, including forming a personal connection with the patient and using active listening techniques. Balancing the challenges and limitations with the benefits of videoconferencing is an essential competency requiring additional research and guidelines. International Registered Report Identifier (IRRID)RR2-10.2196/27940